KONVERSI MIKROBIOLOGIS BATANG POHON SINGKONG (Mannihot esculenta) MENJADI ETANOL OLEH Trichoderma reesei PK1J2 DAN Saccharomyces cerevisiae 3012 - , AFRIYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cassava stems can be utilized as an alternative energy source to produce bioethanol due to its cellulose content, polysaccharide compound can not directly used by yeast. Therefore, cellulose need to be hydrolyzed into monomers prior to tranformation into ethanol by Saccharomyces cerevisiae. Hydrolysis can be performed by cellulase-producing fungi, such as Trichoderma reesei PK1J2 with ammonium sulphate used as nitrogen source. This study purposes were to analyze the effect of ammonium sulphate addition to the growth and reducing sugar production rate of Trichoderma reesei from cassava stems and also to analyze the effect of fermentation method on Saccharomyces cerevisiae ethanol production. Hydrolysis was conducted without pretreatment. Cassava stem was degraded into small pieces with and without addition of ammonium sulphate. The concentration of (NH4)2SO4 were 0%